BCG induced lower urinary tract symptoms during treatment for NMIBC—Mechanisms and management strategies - Bourlotos, Georgia; Baigent, William; Hong, Matthew; Plagakis, Sophie; Grundy, Luke (Frontiers in Neuroscience, 2024)
Non-muscle invasive bladder cancer (NMIBC) accounts for ~70-75% of total bladder cancer tumours and requires effective early intervention to avert progression. The cornerstone of high-risk NMIBC treatment involves trans-urethral resection of the tumour followed by intravesical Bacillus Calmette-Guerin (BCG) immunotherapy. However, BCG therapy is commonly accompanied by significant lower urinary tract symptoms (LUTS) including urinary urgency, urinary frequency, dysuria, and pelvic pain which can undermine treatment adherence and clinical outcomes. Despite this burden, the mechanisms underlying the development of BCG-induced LUTS have yet to be characterised.This review provides a unique perspective on the mechanisms thought to be responsible for the development of BCG-induced LUTS by focussing on the sensory nerves responsible for bladder sensory transduction. This review focuses on how the physiological response to BCG, including inflammation, urothelial permeability, and direct interactions between BCG and sensory nerves could drive bladder afferent sensitisation leading to the development of LUTS. Additionally, this review provides an up-to-date summary of the latest clinical data exploring interventions to relieve BCG-induced LUTS, including therapeutic targeting of bladder contractions, inflammation, increased bladder permeability, and direct inhibition of bladder sensory signalling.Addressing the clinical burden of BCG-induced LUTS holds significant potential to enhance patient quality of life, treatment compliance, and overall outcomes in NMIBC management. However, the lack of knowledge on the pathophysiological mechanisms that drive BCG-induced LUTS has limited the development of novel and efficacious therapeutic options. Further research is urgently required to unravel the mechanisms that drive BCGinduced LUTS.